2015
DOI: 10.1016/j.msec.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Metallic zinc exhibits optimal biocompatibility for bioabsorbable endovascular stents

Abstract: Although corrosion resistant bare metal stents are considered generally effective, their permanent presence in a diseased artery is an increasingly recognized limitation due to the potential for long-term complications. We previously reported that metallic zinc exhibited an ideal biocorrosion rate within murine aortas, thus raising the possibility of zinc as a candidate base material for endovascular stenting applications. This study was undertaken to further assess the arterial biocompatibility of metallic zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 211 publications
(152 citation statements)
references
References 36 publications
(36 reference statements)
7
134
0
1
Order By: Relevance
“…Bowen et al studied the in vivo performance of zinc wires (99.99%) over 6 months when implanted into the abdominal aorta of adult rats [59,80]. They found uniform corrosion with linearly increasing corrosion rates over the residence time.…”
Section: In Vivo Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowen et al studied the in vivo performance of zinc wires (99.99%) over 6 months when implanted into the abdominal aorta of adult rats [59,80]. They found uniform corrosion with linearly increasing corrosion rates over the residence time.…”
Section: In Vivo Examinationmentioning
confidence: 99%
“…In addition, a histological examination indicated excellent biocompatibility with the arterial tissue as well as tissue regeneration within the original footprint of the degrading implant. Intriguingly, observations of low cellular density and a distinct lack of smooth muscle cells adjacent to the implant interface indicates that the Zn 2+ ions released from a zinc implant may suppress restenosis pathways [80]. Yang et al [81] investigated the degradation of pure zinc stents over one year in a rabbit abdominal aorta model.…”
Section: In Vivo Examinationmentioning
confidence: 99%
“…In 2011, Vojtech et al [25] prepared binary Zn-Mg alloys containing Mg content up to 3 wt.%, and found that the binary Zn-Mg alloys exhibited corrosion rates (≈0.018 mm/yr) close to pure Zn, which were significantly lower than those of Mg and AZ91HP alloys. As a breakthrough, Bowen et al [26, 27] examined the corrosion behavior of pure Zn for the first time and found that 1) Zn exhibited excellent biocompatibility after resided in the arterial lumen of Sprague-Dawley rats for 6.5 months; 2) the corrosion products are not potentially hazardous like those of iron; 3) the corrosion rate in the first 2–3 months is very close to the ideal degradation rate for medical implants (0.02 mm/y) [28] and followed by an acceleration in 3–6 months; 4) a uniform corrosion is detected in earlier months so that the corrosion is more or less uniformly distributed over the entire exposed surface and the corrosion proceeds at approximately the same rate over the exposed metal surface [29]. All these corrosion characteristics of pure Zn suggest that Zn arterial corrosion behavior may be superior to other explored materials in the AMS field [24, 27].…”
Section: Introductionmentioning
confidence: 99%
“…A recent histological (in vivo) study by the authors 42 examined pure (99.99%) Zn wires that were implanted in a transluminal fashion in the abdominal aortas of rats, with a large portion of the wire positioned along the endothelium and exposed to blood flow. That study concluded that pure, metallic Zn and its corrosion products were noninflammatory, antiproliferative toward smooth muscle cells, possibly antirestenotic, and did not foster any necrosis or other local toxicity.…”
Section: Introductionmentioning
confidence: 99%